Persuasive business presentations : using the problem-solution method to influence decision makers to take action - May, Gary L. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2014)
Business life is about persuasion. Effective managers advance their careers by identifying problems, developing solutions, and persuading decision makers to provide the support and resources necessary to make things happen. This book focuses on a specific presentation context: a problem-solution persuasive presentation to decision makers delivered in a conference room environment. Such presentations occur at every level in an organization. Therefore, team leaders, supervisors, managers, and executives can all benefit from learning how to design and deliver powerful presentations that move decision makers to take action. The author blends his extensive business experience with current research on persuasion to provide a practical, applied approach to using the problem- solution pattern. An integrated case study provides examples for each step in the process. The result is a useful, actionable guide that will help professionals from every field make a difference in their organization.
Introduction -- Part I. Developing a problem-solution presentation -- 1. Conducting a communication strategy analysis -- 2. Constructing the presentation opening -- 3. Building the body of the presentation -- 4. Closing with power -- Part II. Delivering a problem-solution presentation -- 5. Creating visual support -- 6. Preparing for delivery -- 7. Delivering the presentation -- Notes -- References -- Index.
Part of: 2013 digital library.
Includes bibliographical references (pages 91-92) and index.
Title from PDF title page (viewed on December 16, 2013).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Business presentations; Persuasion (Rhetoric); persuasion; presentation; problem-solution pattern; Electronic books